Usage of major nutrients by modern varieties of spring durum wheat in dependence on predecessor and nutrient background - Попов, С. І.; Цехмейструк, М. Г.; Манько, К. М.; Усов, О. С. (Scientific Progress & Innovations, 2015)
The article highlights two-years’ (2013–2014) experimental data on varietal characteristics of the major nutrients consumption as affected by various predecessors and mineral nutrient background in conditions of the Ukrainian Eastern Forest-Steppe. It was found that variety Novatsiya uptakes the most nutrients for the formation of 1 t of grain. Against the background without fertilizers it uptakes 28 kg of nitrogen, 10 kg of phosphorus and 14 kg of potassium, while against the background of 30 t/ha manure along with application of N60P60K60 – 36 kg of nitrogen, 14 kg of phosphorus and 15 kg of potassium.